Meninjau Ulang Iwadl Khuluk Perspektif Keadilan Gender - Ahmad Rezy Meidina (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2022)
This article examines iwadl khuluk in the perspective of gender justice. Iwadl in fiqh perspective, property that women return to men in order to get their rights because men have paid dowry as a legal consequence of the marriage contract. Whereas in possitive law, the concept of iwadl changed to taqnin, iwadl khuluk which was originally given to men, became or given to the Court based on the regulation of the Minister of Religious Affairs of the Republic of Indonesia Number 411 of 2000 concerning the Determination of iwadl amounting to Rp. 10,000, -. The court judged that the specific costs contained gender justice or called responsive gender. This article abstracts the concept of justice in the cost that women give to men using five gender manifestations: stereotype, double burden, marginalization, discrimination and violence.